Ensinador: Corpus-based Portuguese grammar exercises - Simões, Alberto (2011)
In this paper we describe Ensinador, a tool that creates grammar exercises for teaching Portuguese as a foreign language, at university level, based on large annotated corpora. After discussing the motivation for the tool, and the context in which it was deployed, we present its specification and its implementation, discussing the particular requirements with concrete examples. We report actual use of the tool in teaching, and compare it to other systems in the literature, ending the paper with a short description of future and ongoing related work.